Molecular phylogeny of the genus Rhabdosciadium (Apiaceae) with description of a new species R. anatolyi from Hakkâri province, eastern Turkey - Lyskov, Dmitry; Kljuykov, Eugene; Güner, Ebru Doğan; Samigullin, Tahir (Phytotaxa, 2017)
Six species of the genus Rhabdosciadium (Apiaceae) were studied by molecular phylogenetic analysis. The taxonomic status of each of them has been confirmed, the genus Rhabdosciadium turns out as a well-supported monophyletic group closely related to the genera Aegopodium, Caropodium, Carum, Falcaria, Fuernrohria, Gongylosciadium, Grammosciadium s.s., Hladnikia, Olymposciadium, etc. Rhabdosciadium anatolyi sp. nov. is described and illustrated as a new species from Hakkâri province, eastern Turkey. It differs from the other taxa of the genus, in addition to its unique geographical range, in the large terminal leaf lobes with regularly serrated margin, mainly ternate primary basal segments of leaves, and long internodes.